So rare we need to hunt for them: reframing the ethical debate on incidental findings - Schuol, Sebastian; Schickhardt, Christoph; Wiemann, Stefan; Bartram, Claus R.; Tanner, Klaus; Eils, Roland; Meder, Benjamin; Richter, Daniela; Glimm, Hanno; Kalle, Christof von; Winkler, Eva C. (Genome medicine, 2015)
Incidental findings are the subject of intense ethical debate in medical genomic research. Every human genome contains a number of potentially disease-causing alterations that may be detected during comprehensive genetic analyses to investigate a specific condition. Yet available evidence shows that the frequency of incidental findings in research is much lower than expected. In this Opinion, we argue that the reason for the low level of incidental findings is that the filtering techniques and methods that are applied during the routine handling of genomic data remove these alterations. As incidental findings are systematically filtered out, it is now time to evaluate whether the ethical debate is focused on the right issues. We conclude that the key question is whether to deliberately target and search for disease-causing variations outside the indication that has originally led to the genetic analysis, for instance by using positive lists and algorithms.